Does Conflict Lead to Ethnic Particularism? Electoral Violence and Ethnicity in Kenya 2005–2008. Issue 3 (2nd July 2016) - Ishiyama, John; Gomez, Amalia Pulido; Stewart, Brandon
Abstract : What impact does violence have on ethnic identity? Do acts of violence tend to create greater segmentation and "hardening" of identities among ethnic groups? In this article, we empirically assess the claim that violence inevitably leads to the hardening of ethnic identity (which we operationalize as expressions of ethnic particularism over a national identity). Using survey data from Kenya covering the period 2005–2008, integrated with geocoded data on conflict events in Kenya during that period, and employing multilevel logistic regression analysis, we do not find support for the contention that ethnic identity hardens inevitably as the result of violence. Rather, our findings suggest support for a more nuanced view of the effects of violence on ethnic identity.